Combination of Topic Modelling and Decision Tree Classification for Tourist Destination Marketing - Christodoulou, Evripides; Gregoriades, Andreas; Pampaka, Maria; Herodotou, Herodotos (My University, 2020)
This paper applies a smart tourism approach to tourist destination marketing campaigns through the analysis of tourists’ reviews from TripAdvisor to identify significant patterns in the data. The proposed method combines topic modelling using Structured Topic Analysis with sentiment polarity, information on culture, and purchasing power of tourists for the development of a Decision Tree (DT) to predict tourists’ experience. For data collection and analysis, several custom-made python scripts were used. Data underwent integration, cleansing, incomplete data processing, and imbalance data treatments prior to being analysed. The patterns that emerged from the DT are expressed in terms of rules that highlight variable combinations leading to negative or positive sentiment. The generated predictive model can be used by destination management to tailor marketing strategy by targeting tourists who are more likely to be satisfied at the destination according to their needs.
Keywords: Topic modelling; Sentiment analysis; Decision tree; Tourists’ reviews